The Effect of Sustainable Packaging on Household Shopper Purchase Intent - Munro, Penelope (Auckland University of Technology, 2020)
Packaging was introduced to consumers as a way to protect goods, as well as to help ease handling and clearly communicate the contents of items being purchased (Lindh et al., 2016). However today, one of the most common forms of packaging, plastic, has become a threat to environmental health by contributing greatly to waste (Ellen MacArthur Foundation, 2019; World Commission on Environment and Development (WCED), 1987; WasteMINZ, 2020). Some consumers are turning to reduced-packaging options such as package-free shampoo bars, and are stating a preference for sustainable packaging (Business Wire, 2019). But are consumers concerned enough about the consequences of plastic packaging to change their grocery shopping habits? This research sought to understand the effect of information about disclosing the macro environmental impact of packaging on individual household shopper purchasing behaviour. In this quantitative research, an experiment compared the purchase intent of household shoppers after they viewed labelling options which revealed the sustainability (or not) of packaging of common grocery store items. This study was conducted using an online panel of New Zealanders, recruiting 204 participants aged 20-plus years. Respondents were randomly assigned one of three groups that saw labels as a tech overlay on an e-commerce site: (1) control with no label, (2) the Packaging Star label, and (3) the Australasian Recycling label. The stimuli for the study was a replica of an online shopping page from a well-known New Zealand supermarket chain. Two high volume food grocery categories were chosen, peanut butter and milk. Within each category, shoppers were presented with six product options mocked up from the supermarket site, complete with product visual, product description and price. For the control group, no additional information was added. However, for the two sustainable packaging options, a brief description and symbol was added to show how each product’s packaging was or was not recyclable (Australasian Recycling Label) or how sustainably produced and recyclable (Packaging Star label) the items’ packaging was. All three groups of participants were then asked questions about which product they would buy, their level of sustainable knowledge, their attitudes to sustainable packaging and some general demographic questions. Statistical analysis using ANVOA and regression analysis was then conducted to analyse the findings. Does disclosing packaging sustainability impact consumer choice? The overall result was that there was no significant relationship found between the introduction of sustainable packaging information labels and the corresponding selection of the product with the most sustainable packaging. Yet, tests via Hayes’ PROCESS moderation show that a shopper’s level of sustainable knowledge is a moderating factor that increased purchase for more (vs. less) sustainably packaged peanut butter. There was no moderating effect for the sustainable attitudes consumers held, though a majority of respondents indicated holding strong sustainable attitudes. Another clear moderator emerged, showing that those who value aesthetics in packaging design were more likely to choose products with more (vs. less) sustainable packaging. However, packaging design might not be a factor that consumers generally use to make final purchase selections. Overall, packaging design features was ranked the least important overall factor in product choice by respondents, with price, taste and quality as higher rated attributes. Disappointingly for the practice of sustainable consumption and planetary effects, this study shows that the mere presence of sustainable packaging information on an e-commerce grocery shopping site did not impact household shoppers’ purchase decision. The study contributes to the current body of knowledge in that it reinforces the literature around the existence of an attitude behaviour gap in sustainable consumption (Dilkes-Hoffman et al., 2019; Joshi & Rahman, 2015; Nguyen et al., 2020; Rokka & Uusitalo, 2008; Thøgersen et al., 2010; White et al., 2019). However it does shed light on the role that sustainable knowledge, which was reflected in the literature, has in closing that gap, where people who have understanding versus feeling about the effects of the environmental issues such as plastic pollution and climate change are more likely to show preference for sustainable packaged products. (Dekhili & Achabou, 2014; Rokka & Uusitalo, 2008; Taufique et al, 2015; Thøgersen et al., 2010). The study also found that where a person resides may have a moderating affect, in that those who live in metropolitan cities are more likely to purchase sustainable products. The study looked at online shopping environment which offers household shoppers an environment where they possibly have more time to consider purchases. To the knowledge of this researcher this context has not previously been researched. Therefore, the answer to encouraging household shoppers to select products with sustainable packaging is more complex than just informing them or relying on their sustainable attitudes. Based on these findings, the first key to household grocery consumer change might be to increase and promote overall knowledge of sustainable cause-and-effects. Even broader still is a macro marketing approach of combining government initiatives such as a ban on plastic bags along with manufacturer efforts, such as Coca-Cola’s recent investment in 100% recycled plastic bottles, to create meaningful sustainable packaging choice change.
Keywords: Sustainable packaging; Online shopping; Household shopper; Sustainability